Repercussions of the pandemic of COVID-19: care of the pediatric population in Primary Health Care - Shibukawa, Bianca Machado Cruz (2022)
Objective: to describe the repercussions of the COVID-19 pandemic on the care of the pediatric population in Primary Health Care. Methods: qualitative study conducted with 28 primary care coordinators linked to a regional health region. Data were imported into the NVivo Release Program for content analysis. Results: there was a reduction of access to primary care for actions of prevention and promotion of child health, intensifying assistance based on the biomedical model to the detriment of surveillance of child development as well as the need for (re)organization of assistance through new strategies. Conclusion: the pandemic had a negative repercussion on child health care represented by the reduction in demand and pediatric demand in Primary Health Care, however, it was identified that services were reorganized through new appointments and tele-attendance to maintain the principles of primary care and the Brazilian Unified Health System. Contributions to practice: the study enabled the identification of new forms of health organization regarding the care of children in primary care in the context of the COVID-19 pandemic. Because, the use of telehealth can contribute to the monitoring of children in other realities.